1982
DOI: 10.1104/pp.70.5.1544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pod Removal on Leaf Senescence in Soybeans

Abstract: Senescence of soybean leaves is characterized by a decline in photosynthesis and the loss of leaf protein and Chl (11,22). Clearly, the most dramatic visual symptom is leaf yellowing, and because of this, it is widely used as an index of plant and leaf senescence. From our field studies with winter wheat (21) and soybeans (22), loss of Chl appears to be a good initial index of leaf senescence. Yet caution must be taken in using this as the only indicator of senescence since Chl loss is not always an inevitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
2
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 15 publications
(13 reference statements)
5
72
2
1
Order By: Relevance
“…Analysis of photosynthetic processes revealed that carbon fixation rates declined progressively from the time of full leaf expansion (Figure 4). This age-related, progressive loss of photosynthetic function from the time of leaf maturity may be a general feature of annual plants because this phenomenon has been observed in cucumber (Callow, 1974), Perilla (Batt and Woolhouse, 1975), barley (Friedrich and Huffaker, 1980), wheat (Peoples et al, 1980), maize (Crafts-Brandner et al, 1984a), and soybean (Wittenbach, 1982;Ford and Shibles, 1988). Wittenbach referred to the photosynthetic decline as "functional senescence" to distinguish this process from the subsequent rapid loss of chlorophyll and macromolecular turnover associated with the senescence syndrome (Wittenbach, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of photosynthetic processes revealed that carbon fixation rates declined progressively from the time of full leaf expansion (Figure 4). This age-related, progressive loss of photosynthetic function from the time of leaf maturity may be a general feature of annual plants because this phenomenon has been observed in cucumber (Callow, 1974), Perilla (Batt and Woolhouse, 1975), barley (Friedrich and Huffaker, 1980), wheat (Peoples et al, 1980), maize (Crafts-Brandner et al, 1984a), and soybean (Wittenbach, 1982;Ford and Shibles, 1988). Wittenbach referred to the photosynthetic decline as "functional senescence" to distinguish this process from the subsequent rapid loss of chlorophyll and macromolecular turnover associated with the senescence syndrome (Wittenbach, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…This regulatory feature may be the critical one that distinguishes Arabidopsis from other monocarpic plants such as soybean, in which the senescence syndrome is correlatively controlled by reproductive development. Interestingly, depodding of soybean plants will delay the final stages of senescence in the leaf but does not prevent photosynthetic decline (Wittenbach, 1982;CraftsBrandner et al, 1984b). In fact, the Rubisco enzyme may be degraded in leaves of depodded plants, but the mobilized N is apparently refixed in the paraveinal mesophyll as storage protein (Franceschi et al, 1983;Wittenbach, 1983).…”
Section: (C) Rbcs (D) Ef-1a (E) Sag2 (F)sag4mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of an altered reproductive sink demand on accumulation of VSP have been limited to studies of soybean (5,18,19,25,26). Because depodding, JA, and MeJA elicit similar VSP accumulation responses in soybean, other monocarpic annuals that express MeJA-induced proteins also may accumulate proteins with VSP characteristics when reproductive sink demand is altered.…”
mentioning
confidence: 99%
“…plants, abundant levels of the same specific vegetative proteins (molecular masses of 27, 29, and 94 kD) accumulate predominantly in the vacuoles of PVM cells of leaves (5,7,18,19,21). The 94-kD protein was recently identified as a member of the vegetative lipoxygenase family and proposed to be a bifunctional zymogen capable of catalyzing the hydroperoxidation of lipids and storing excess N temporarily (21).The effects of an altered reproductive sink demand on accumulation of VSP have been limited to studies of soybean (5,18,19,25,26). Because depodding, JA, and MeJA elicit similar VSP accumulation responses in soybean, other monocarpic annuals that express MeJA-induced proteins also may accumulate proteins with VSP characteristics when reproductive sink demand is altered.…”
mentioning
confidence: 99%